KOMUNIKASI RISIKO HIV DAN AIDS BAGI KELOMPOK REMAJA GAY DI JAKARTA - Slamet Widadi (Universitas Mercu Buana, 2017)
Current information related knowledge of HIV and AIDS is not yet a priority need and not fully accessible to teenagers. They prefer the latest information and modern related to life style or lifestyle. The focus of this research is